Population Development and Disease Incidence of Virus Disease Transmitted by Brown Planthopper on the Paddy Field Applied with Biofertilizers and Biopesticides - Widiarta I. Nyoman; Pratiwi Etty; Wardana I. Putu; Purwanto Oky Dwi (E3S Web of Conferences, 2023)
Demand for biofertilizers and biopesticides are increasing in line with rising public consent on healthy food and environmental safety. Biofertilizer and biopesticide for rice have been formulated and those necessary to be tested in the field. The objectives of this field experiment were to test the effect of the formulation on the population development of brown planthopper (BPH) - Nilaparvata lugens (Stål, 1854) and the virus they transmitted. Split-plot design experiment was conducted in the farmer paddy fields. The main plot was varieties and biofertilizer and biopesticide were used as subplot. The population of BPH and natural enemies were surveyed using sweep net. The viral infected plant was checked by using iodine-test, while virus disease symptom was observed visually parallel with population census. The results showed that BPH utilized rice nursery as refugee during pre-rice transplanting. Reproduction rate of invading generation to the first generation on the Prb and Agm treated plots were lower than other treatments. The Agm application reduced virus disease symptom during the vegetative stage and kept virus-infected lower than other treatments in the early generative stage. Inpari 42 variety has a high ability to suppress the level of viral infection to be disease symptoms. It indicated that Agm was not only function as a biofertilizer but also biopesticide and can be integrated with Inpari 42 to manage rice virus diseases transmitted by BPH.